KAJIAN PENGEMBANGAN TAMBAK GARAM DI PULAU TANAKEKE KABUPATEN TAKALAR - Jusran Jusran; Muhammad Kasnir; Abdul Rauf (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
Salt is one of the national strategic commodities. But until now the notional needs of salt have not been met by national salt production in the country, one of the efforts to increase salt production in the country is to optimize existing potential salt field. The island of tanakeke in takalar district of southern sulawesi province has a potential salt field, wich is not yet well watered. The reseach’s aims (1) to anayize potential land appropriations for the development of salt pans on tanakeke island (2) to analize the salt-farm development cost (3) to determine salt pond development strategies based on the characteristics of the research area. Research suggetts that the total potential land most suitable for development of salt pond at 1.106,58 ha or about 38,91 % of the total land on Tanakeke islands. Based on the financial analysis of the salt pond with geomembran method on an acre of land on tanakeke islands are feasible to continue. Followed by the investment criteria acquired by NPV>1, Net B/C>1 and IRR>discount rate. Selected combination of strategies (1) Priority strategies; Training in increased human resource capacity and Infrastructure improvements. (2) altenative strategies; salt regulatory improvements.